Data management plans: time wasting or time saving?. (3rd June 2020) - Nightingale, Alison
Abstract : As a Research Data Librarian, one of my responsibilities is to raise awareness about the requirements for academic researchers to write data management plans for their projects. These awareness activities, often in the form of a presentation at staff meetings or departmental seminars, are frequently followed by a sceptical response from the academic staff along the lines that "This is just something else for us to try to fit into our already over-busy lives". My answer is usually: "Yes, but it might prevent data management problems slowing up your project". So, what are data management plans and how can they be of value to your project?